Pandangan Kognitifisme dan Aplikasinya dalam Pembelajaran Pendidikan Agama Islam Anak Usia Dini - Nugroho, Puspo (THUFULA, 2015)
Early Childhood Education becomes a very important phase of education.Phase which will color the world of children’s cognitive thinking. In this phase ofbrain development in children achieve the remarkable level, which in this phasethe child reaches the golden era (golden age) so that the child is able to developthe power of perception based on what is seen, heard and felt, so that the childwill have a thorough understanding and comprehensive. From that some figuressuch as Jerrome Brunner, Ausabel and Jean Piaget contributed cognitive learningstyle and thinking according to each, According to Jerome Bruner in the learningprocess is more determined how the teacher is able to organize learning accordingto the student’s learning style. The students are learning according to Ausubelmust be “meaningful” (meaningfull). Meaningful learning is a process where newinformation, in which new information is associated with the structure of therelevant concepts, cognitive structure that is already owned by someone learners.Meanwhile, according to Jean Piaget every child develops the capacity to thinkin an orderly phase. At a certain stage of development will emerge schemes orcertain cognitive structures whose success at each stage is highly dependent on theprevious stage. Of the three characters are interrelated and complementary. Thirdapplication of the above theory in PAI learning, especially for young children, ateacher needs to know in depth protege start developmentally age, style oflearning styles, as well as in packaging materials must be meaningful, it means tohave linkages with prior knowledge of children, use of media educative abstract tostimulate the understanding, delivery of content delivered ranging from the simpleto the complex, the learning process needs to be developed based activities, etc.Through these principles is expected socio-emotional development, intelligenceand personality of children will grow up.